Standardized learner simulation for debriefer training through video conference - Jiyoung Rhee; Hyun Soo Park (Korean Journal of Medical Education)
Purpose Debriefing after simulation-based healthcare education (SBHE) is challenging. Educators’ debriefing skills are essential to the success of learning. For debriefing skill training, we designed a simulation course with the standardized learner (SL) through video conference. The purpose of this study was to describe the implementation process of the SL simulation course and evaluate its effectiveness on educators’ self-confidence and debriefing skills. Methods This simulation course involved six trainees and two trainers. After watching a 5-minute sample video of SBHE, each trainee conducted their role as a debriefer in this video and the trainer acted as a learner (SL) in this video. Following each simulation, individual feedback by the trainer was immediately implemented. To evaluate the course’s effectiveness, trainees’ self-confidence questionnaire was collected, and objective structured assessment of debriefing (OSAD) scores were evaluated. Results After completing five SL simulation sessions in 2 weeks, the trainees’ self-confidence level and OSAD scores improved significantly (estimate=0.114, standard error=0.020, p<0.001, and p=0.006). Conclusion This debriefer training course using SL simulation via video conference could improve self-confidence and debriefing skills of trainees. This SL simulation can be used as a new and flexible method for training debriefers.